2010
DOI: 10.1038/oby.2010.13
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association Between PCK1 Polymorphisms and Obesity, Physical Activity, and Fitness in European Youth Heart Study (EYHS)

Abstract: Phosphoenolpyruvate carboxykinase‐1 (PCK1) is the rate‐limiting enzyme in the hepatic gluconeogenic pathway. Studies have shown that overexpression of Pck1 in mice results in obesity‐related traits and higher levels of physical activity (PA). Therefore, our aims were to investigate whether common genetic variation in the PCK1 gene influences obesity‐related traits, PA, and fitness, and to examine whether PA and fitness attenuate the influence of the PCK1 polymorphisms on obesity in children. Analyses were unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Phosphoenolpyruvate carboxykinase-1 (PCK1) was reported to participate in lipid metabolism 47 , is the rate-limiting enzyme in hepatic gluconeogenic pathways, and is closely related to obesity 48 . PCK1was also involved in pathways of glucose metabolism and pyruvate metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphoenolpyruvate carboxykinase-1 (PCK1) was reported to participate in lipid metabolism 47 , is the rate-limiting enzyme in hepatic gluconeogenic pathways, and is closely related to obesity 48 . PCK1was also involved in pathways of glucose metabolism and pyruvate metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…IGF2 [632], RPPH1 [633], PRKCB (protein kinase C beta) [634], CCL5 [635], VASH2 [636], GREM1 [637], CYP11B2 [638], HIC1 [639], PCK1 [640], HSD11B2 [641], MME (membrane metalloendopeptidase) [642], FABP1 [142], MIOX (myo-inositol oxygenase) [643], ARG2 [644], PPARGC1A [645], VNN1 [646], NOX4 [647], EPHX2 [577], DDIT4 [648], SLC2A1 [649], PFKFB2 [650], CDH2 [651], SLC22A2 [294], AQP2 [652], ANGPT1 [653], KL (klotho) [654], ACE2 [655], STC1 [656], REN (renin) [608], ERRFI1 [657], ERBB4 [658], NTNG1 [659], VCAM1 [660], PTGER3 [661] and BBOX1 [662] expression levels are associated with diabetic nephropathy. IGF2 [663], IRF7 [664], PRKCB (protein kinase C beta) [665], CCL5 [666], ACTN3 [667], AMH (anti-Mullerian hormone) [668], E2F1 [669], UBE2M [670], TP73 [671], AGER (advanced glycosylation end-product specific receptor) [672], SMPD3 [118], NR2E1 [673], ANGPTL3 [674], CYP3A5 [675], PCK1 [676], LRP2 [677], FABP1 [678], SLC22A12 [279], CYP8B1 [679], MIOX (myo-inositol oxygenase) [680], ARG2 [681], FGF1 [450], CRY1 [682], PPARGC1A [451], CRYM (crystallin mu) [683], SLC19A3 [283], FH (fumaratehydratase) [684], SLC2A9 [286], GC (GC vitamin D binding protein) [685], RGN (regucalcin) [686], MMAA (metabolism of cobalamin associated A) [687], NOX4 [688], ABHD6 [689], EPHX2 [690], DDIT4 [691], EGF (epidermal growth factor) [173], DEFB1 [692], ACE2 ...…”
Section: Discussionmentioning
confidence: 99%
“…Any abnormality in the kinase product produced at the transcriptional or translational level may lead to diabetes. Vimaleswaran [ 36 ] et al have found that PCK1 gene polymorphism is not associated with obesity in European adolescents. Rees [ 37 ]et al have discovered that rs1042531 is not associated with T2DM in South Asian populations.…”
Section: Discussionmentioning
confidence: 99%